2010
DOI: 10.1103/physreve.81.030901
|View full text |Cite
|
Sign up to set email alerts
|

Basins of attraction for species extinction and coexistence in spatial rock-paper-scissors games

Abstract: We study the collective dynamics of mobile species under cyclic competition by breaking the symmetry in the initial populations and examining the basins of the two distinct asymptotic states: extinction and coexistence, the latter maintaining biodiversity. We find a rich dependence of dynamical properties on initial conditions. In particular, for high mobility, only extinction basins exist and they are spirally entangled, but a basin of coexistence emerges when the mobility parameter is decreased through a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…Another interesting phenomenon to consider that is directly related to mobility is epidemic spreading. The effects of epidemic spreading on species coexistence in a spatial RPS game have been studied in [51,54,141]. It has been shown that in the absence of epidemic spreading, there exist extinction basins that are spirally entangled for m > m c , while basins of coexistence emerge for m < m c .…”
Section: B Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting phenomenon to consider that is directly related to mobility is epidemic spreading. The effects of epidemic spreading on species coexistence in a spatial RPS game have been studied in [51,54,141]. It has been shown that in the absence of epidemic spreading, there exist extinction basins that are spirally entangled for m > m c , while basins of coexistence emerge for m < m c .…”
Section: B Mobilitymentioning
confidence: 99%
“…It has been shown that in the absence of epidemic spreading, there exist extinction basins that are spirally entangled for m > m c , while basins of coexistence emerge for m < m c . Moreover, it has been discovered that intra-species infection promotes coexistence, while inter-species spreading fails to evoke the same effect [51,54,141].…”
Section: B Mobilitymentioning
confidence: 99%
“…Phase transitions and selection have also been studied in the predator-prey models allowing some motion throughout inhabitable vacant sites [13,14]. Recent theoretical studies focused on biodiversity and the emergence of self-organizing patterns by competing associations with homogeneous and heterogeneous invasion rates [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], elevating models of cyclical interactions to an enthusiastically approached field of research.…”
Section: Introductionmentioning
confidence: 99%
“…Rock-paperscissors (RPS)-type models incorporate some of the crucial ingredients associated with the dynamics of a network of competing species; they have been used as powerful tools in the study of complex biological systems. In its simplest form, the RPS game describes the evolution of three species that cyclically dominate each other [1][2][3] (see also Refs. [4,5] for the pioneer work by Lotka and Volterra).…”
mentioning
confidence: 99%